The Dynamics of Financial Crises and the Risk to Defend the Exchange Rate - Christian Bauer; Bernhard Herz (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2009)
Despite major recent advance in the literature on financial crises, the key role of central banks in the dynamics of financial crises are still not well understood. Our aim is to contribute to a better understanding of the dynamics of financial crises by explicitly modeling the strategic options of both traders and central banks. We analyze a global game in which both speculative traders and the central bank face imperfect information. In case of an attack, the central bank basically faces three alternatives. It can either give in to the speculative attack or it can try to defend its exchange rate regime. If it chooses to defend its currency, the defense can be successful or not. In accordance with stylized facts for emerging markets, immediate devaluations are associated with costs in terms of higher (imported) inflation, successful interventions are followed by sluggish growth due to the underlying restrictive monetary policy while unsuccessful interventions typically result in both high inflation and a recession. Taken together, intervention is risky. If a central bank chooses to defend its currency it can avoid the costs of a devaluation in case the defense is successful. However, if it fails it faces the even higher costs of an (unsuccessful) defense and a devaluation, i.e. higher inflation and lower growth. In our global game approach, the strength of the realized defensive measures - in contrast to the potential defense - in general does not monotonously increase with the fundamental state. Thus global games attack models need to take into account the difference between the fundamentals themselves .i.e. the strength of the status quo or the defensive potential .and the optimal central bank reaction to an attack, i.e. the realized defensive measures.
Keywords: F31; D82; E42; 330; currency crises; monetary policy; global game; imperfect information